Phase‐Specific Hemodynamic Criteria and Outcomes in Patients With Cardiogenic Shock Receiving Percutaneous Ventricular Assist Devices - Yuki Ikeda; Keita Saku; Jun Nakata; Takashi Unoki; Takeshi Yamamoto; Tomohiro Sakamoto; Junya Ako (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Standardized protocols with optimal hemodynamic targets for percutaneous ventricular assist device (PVAD) management remain undefined. We aimed to evaluate the proportion of phase‐specific hemodynamic criteria achieved during PVAD support and their association with outcomes in patients with cardiogenic shock. Methods This multicenter retrospective study enrolled patients with cardiogenic shock requiring PVAD (Impella). Patients were evaluated at 24 hours post‐PVAD, venoarterial extracorporeal membrane oxygenation weaning, and PVAD weaning. Hemodynamic criteria consisted of key targets, including mean arterial pressure ≥60 mm Hg, lactate <2.0 mmol/L, right atrial pressure <15 mm Hg, pulmonary artery wedge pressure <20 mm Hg, pulmonary artery pulsatility index ≥1.0, and cardiac power output ≥0.6 W. The primary outcome was a composite of 30‐day all‐cause mortality and unplanned mechanical circulatory support reintroduction. Results A total of 501 patients were enrolled: 206 (41%) with PVAD alone and 295 (59%) with PVAD and venoarterial extracorporeal membrane oxygenation. The majority of patients were supported with Impella CP (406, 81%). Fulfillment of criteria was observed in 37%, 52%, and 45% at 24 hours post‐PVAD, venoarterial extracorporeal membrane oxygenation weaning, and PVAD weaning, respectively. Patients with unfulfilled criteria at each evaluation point were at high risk for the primary outcome (hazard ratio, 3.2 [95% CI, 2.1–4.8]; hazard ratio, 2.1 [1.2–3.7]; and hazard ratio, 2.0 [95% CI, 1.1–3.6]). Hemodynamic criteria achievement consistently stratified the risk of the primary outcome across different subgroups, including shock cause, shock stage, and concomitant use of venoarterial extracorporeal membrane oxygenation. Conclusions Phase‐specific hemodynamic criteria are often unmet and are associated with significantly higher risks of short‐term fatal events.